Syair Doa Keselamatan Dalam Sedekah Laut Jepara Di Masa Pandemi - Sri Indrahti (Endogami: Jurnal Ilmiah Kajian Antropologi, 2021)
Monel handicrafts grow and develop in Jepara district. It has characteristic that the skill of making monel art is preserved from generation to generation. Its ability to survive was influenced by how much the support of community. Community care and love for the craft can support the existance and development of monel handicraft. The process of descending monel crafts has the advantage that each family as a monel craft business unit has its own characteristics and competitiveness. On the other hand, there is no formal container for learning these skills. This makes monel crafts less open to a wider regeneration process. Even though regeneration really determines the development in the future. Looking at the current development of the craft, efforts to make a more open regeneration process seem necessary. Through this paper, the author try to find steps that can be taken by the supporting community and the Regional Government to form a formal and informal container. It is intended that interested people have access to learn about this craft. Regeneration is carried out to maintain the continuity and development of monel crafts.